MPC-06 Cutting-edge of Cancer Genomic Medicine for brain tumors. (28th November 2020) - Mizoguchi, Masahiro; Hata, Nobuhiro; Kuga, Daisuke; Hatae, Ryusuke; Sangatsuda, Yuhei; Fujioka, Yutaka; Takigawa, Kosuke; Funakoshi, Yusuke; Koga, Yuhki
Abstract: Kyushu University Hospital was designated a Cancer Genome Core Hospital in April 2018, and the multi-gene panel test has been introduced since August 2019. The expert panel has been held for 21 cases of the central nervous system (11 adult glioma, 5 pediatric brain tumors, 5 extramedullary tumors). Actionable gene abnormalities were newly detected in two cases. First case is epithelioid glioblastoma with BRAF V600E mutation, and second is embryonal tumor with VCL-ALK fusion. For the first case, BRAF/MEK inhibitor can be used by the prospective trial of patient-proposed healthcare services with multiple targeted agent based on the result of gene profiling by multigene panel test (NCCH1901). For the second case, we are planning to introduce ALK inhibitor by indicator-initiated clinical trial while continuing ICE therapy. The current approved agents for tumor-agnostic treatment are immune checkpoint inhibitors for mismatch repair deficient (dMMR) cases and TRK inhibitors for NTRK fusion gene-positive cases. We selected microsatellite instability (MSI) test and immunostaining of MMR gene for the indication of immune checkpoint inhibitor for recurrent glioma and Lynch syndrome that require dMMR evaluation, but FoundationOne CDx (F1CDx) allows simultaneous evaluation of MSI and MMR gene abnormalities. Regarding the indication of TRK inhibitors, F1CDx assay is selected as a companion diagnosis for ALK, NTRK1/2/3 fusion gene analysis for pediatric cases. At present, the actionable gene abnormalities are detected by multi-gene panel tests in about 10% of brain tumors. Development of tumor-agnostic treatment will expand the molecular target therapy for brain tumor in the future. Based on the experience of different schemes for molecular targeted therapy, it became clear that it is necessary to establish a cancer genome medical system for prompt introduction of precision medicine for highly malignant brain tumors.